The Effect of Formative Assessment on Self-Regulated Learning Among Grade XI Students at Riyadlul Ulum Wadda’wah Condong - Tarsono; Anisa, Hafilda; Khomah, Isti; Fahrurozi, Anis; Mutmainnah Binti Md Noor, Nur (Universitas Islam Negeri Raden Intan Lampung, 2025)
Formative assessment plays a critical role in enhancing students' self-regulated learning (SRL) by providing continuous, constructive feedback that supports their learning processes. This study investigates the effect of formative assessment on SRL among Grade XI students at Pondok Pesantren Riyadlul Ulum Wadda’wah Condong, addressing a gap in research within pesantren contexts. Using a quantitative associative approach with a survey design, the study involved a sample of 49 students, selected through random sampling based on the Isaac and Michael formula at a 10% margin of error, drawn from a population of 171 students. Data were collected via a Likert-scale questionnaire assessing formative assessment practices and SRL. Validity and reliability tests confirmed that all items were valid, with an r-count greater than r-table (0.2377). The data were analyzed using Pearson's correlation test and partial regression coefficient (t-test). The results indicated a strong positive correlation (0.702) between formative assessment and student independence. The t-test revealed a significant effect (t-count = 6.856, p = 0.000), confirming the acceptance of the alternative hypothesis (Ha). These findings suggest that formative assessment positively influences students' ability to manage their learning independently, particularly in goal setting, time management, and progress evaluation. This research highlights the importance of integrating formative assessment more actively to enhance SRL skills and provides recommendations for adapting learning strategies in pesantren settings.